A case of acute discitis following spinal anaesthesia: a rarity or a tip of the iceberg? - Koirala, Siddhartha; Lamichhane, Suraj; Karn, Navin (Journal of Society of Anesthesiologists of Nepal, 2017)
Acute discitis, an inflammatory process of the intervertebral disc, has been reported as a rare complication of bacterial infection or chemical or mechanical irritation most commonly following spinal surgery. It may extend into the adjacent tissue and lead to grave orthopaedic and neurological consequences. Although it has been reported as an infective complication following spinal anesthesia also, its true incidence in our part of the world is not known. It may be higher than generally thought as the technique is overwhelmingly used. Further, we do not know about its awareness among anesthesia practitioners. Here we report a case of acute discitis in a young lady who presented with severe acute low back pain two weeks after spinal anesthesia for caesarean section; magnetic resonance imaging of lumbosacral spine revealed infective spondilodiscitis and she was treated with antibiotics and analgesics. The true incidence of acute infective discitis following spinal anaesthesia in our part of the world is unknown and it may be higher that thought. It can be prevented by using rigorous aseptic techniques, and anesthesia should be administered by appropriately qualified and trained personnel.